PENGARUH GAYA BAHASA GAUL TERHADAP GENERASI ALPHA DI KELAS 4 DI SEKOLAH DASAR LABORATORIUM UNG - Sri Alfiani Labaco; Lidya Angelyna Putri Kadir; Tisha Azzahra Kusuma; Nadya Dinata Thamrin; Mohamad Arief Neno; Sulfiyanti Saputri Kasim (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study aims to analyze the influence of slang style on alpha generation students in grade 4 of SD Laboratorium Gorontalo State University (UNG). The alpha generation is known as a generation that grew up in the digital era with easy access to information, including the adoption of slang. Slang, although it enriches language creativity and becomes a means of self-expression, can cause an imbalance in students' ability to use formal language. The research used a descriptive qualitative approach through observation and interviews. The results show that the use of slang by students has a positive impact in enhancing language creativity, but can hinder the mastery of formal language, especially in academic contexts. Teachers have an important role in directing language use according to norms and contexts, so that students can balance between creativity and good formal language use.